Analisis Bandwagon Effect Dan Atribut Produk Terhadap Keputusan Pembelian Produk Skincare Pada Generasi Z Di Kota Palangka Raya - Tiurmaulina Nainggolan; Luluk Tri Harinie; John Budiman Bancin; Lelo Sintani (Jurnal Economic Resource, 2026)
This study examines the effect of the bandwagon effect and product attributes on purchase decisions of skincare products among Generation Z in Palangka Raya City. The research aims to analyze the association among the studied variables. A quantitative associative approach was applied using a survey method and analyzed with SmartPLS. The results indicate that the bandwagon effect and product attributes are positively associated with purchase decisions, although their effect levels vary. These findings imply the importance of social trend based marketing strategies and strengthening product attributes to enhance Generation Z purchase decisions